A framework for the adoption of Hackathon for teaching and learning of computer programming - Oyetade, Kayode Emmanuel (Vaal University of Technology, 2022)
Hackathons originated from the evolution and revolution of computers. They were primarily designed as a collaborative tool for solving computer-related tasks or theorising new possibilities based on specific infrastructures. With the prevalence of technology and the drive for digital evolution, the role of hackathons becomes increasingly essential, making its presence known in almost every domain with the potential to transform the business world and society at large. However, hackathons in the educational domain cannot be understood in the same way as their counterparts in a purely business or career-driven domain because of their special nature. Given that educational institutions in South Africa are still in the early stages of using hackathons, studying factors affecting hackathon adoption for teaching and learning computer programming is critical and timely. The research aimed to investigate and find factors that had a bearing on hackathon adoption for teaching and learning computer programming. To realise the aim, a systematic literature review was conducted. Then, a conceptual framework was developed that has its variables (attitude (ATT), effort expectancy (EE), facilitating conditions (FC), perceived usefulness (PU), relative advantage (RA), performance expectancy (PE), perceived ease of use (PEOU), subjective norm (SN), and behavioural intention (BI)) based on an extensive literature review. A questionnaire-based survey was conducted to test the model. The web-based questionnaire was administered to two hundred forty-nine (249) South African Information Technology programming students. Reliability of variables was measured, and all the variables had a co-efficient of 0.7 and greater. Factor analysis was applied and the PEOU failed to fulfil the requirement and so it was dropped. Descriptive and inferential statistics were applied to further analyse the data collected. The correlation result indicated that all the remaining variables in the conceptual framework are significant and have a positive relationship PU (𝑟=0.615), RA (𝑟=0.657), PE (𝑟= 0.597), SE (𝑟=0.660), ATT (𝑟=0.440), EE (𝜌<0.520), SN (𝑟= 0.441), and FC (𝑟=0.357) have a positive relationship with behavioural intention (𝜌<0.001) to adopt hackathon. The regression result indicated that the following variables (PU (𝛽=0.141,𝜌=0.036), RA (𝛽=0.142,𝜌=0.045), PE (𝛽=0.205,𝜌=0.002) and SE (𝛽=0.330,𝜌=0.000) have a positive influence on students’ hackathon adoption. The research study managed to validate the conceptual framework indicating variables that influence or have a relationship with BI. The developed framework forms the main contribution of this research study. The developed framework can be used to assist educators with the variables that have a strong bearing on the adoption of hackathon in education. The adoption of hackathon in education will contribute towards transforming the learning environment from a teacher-centred to a learner-centred one by facilitating a form of social learning where knowledge is created amongst students when interacting, thereby, building relationships, and supporting the learning that happens from cooperation, dependence and helping each other. In conclusion, the introduction of hackathons in education in computer programming can revolutionise the programming landscape in South Africa and around the world during this period of the fourth industrial revolution.
PhD. (Department of Information and Communication Technology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Computer programming; Hackathon; Learning; Teaching; Technology; Adoption; Dissertations, Academic -- South Africa.; Computer programming -- Study and teaching.